Transforming healthcare: a safety imperative. Issue 6 (2nd December 2009) - Leape, L; Berwick, D; Clancy, C; Conway, J; Gluck, P; Guest, J; Lawrence, D; Morath, J; O'Leary, D; O'Neill, P; Pinakiewicz, D; Isaac, T; et al.
Abstract : Ten years ago, the Institute of Medicine reported alarming data on the scope and impact of medical errors in the US and called for national efforts to address this problem. While efforts to improve patient safety have proliferated during the past decade, progress toward improvement has been frustratingly slow. Some of this lack of progress may be attributable to the persistence of a medical ethos, institutionalized in the hierarchical structure of academic medicine and healthcare organizations, that discourages teamwork and transparency and undermines the establishment of clear systems of accountability for safe care. The Lucian Leape Institute, established by the US National Patient Safety Foundation to provide vision and strategic direction for the patient safety work, has identified five concepts as fundamental to the endeavor of achieving meaningful improvement in healthcare system safety. These five concepts are transparency, care integration, patient/consumer engagement, restoration of joy and meaning in work, and medical education reform. This paper introduces the five concepts and illustrates the meaning and implications of each as a component of a vision for healthcare safety improvement. In future roundtable sessions, the Institute will further elaborate on the meaning of each concept, identify the challenges to implementation, and issue recommendations for policy makers, organizations, and healthcare professionals.